Artificial intelligence, illegalised mobility and lucrative alchemy of border utopia - Milivojevic, Sanja (Criminology & criminal justice, 2025)
Artificial intelligence (AI) has captured the interest of academia and a range of industries. Much of this appeal is driven by the obsession with military and political supremacy, and a desire to control people and their movements. This article looks at the expansion and impact of AI systems deployed along physical borders on the mobility of illegalised non-citizens and border security in the Global North. Using the case study of Silicon Valley’s Anduril, the article focuses on the US–Mexico border and assesses AI’s role in hindering illegalised mobility and reconfiguring border control. Two key contributions are made in the paper. First, AI advances must become the focus of border criminologies, examined within the milieu from which the technology emerged. Second, virtual walls are commercial, political and anti-humanitarian. They are opaque, resembling alchemy, flawed but with profound consequences. The article adds to the debate on whether AI experiments should be permitted in border control.